Public sector investment planning for developing countries - Fitzgerald, E. V. K. (London : Macmillan, 1978)
This book is the product of postgraduate teaching of and professional experience in the analysis of public investment in developing countries over a number of years.
Includes index.
Includes bibliographical references p. 192-196 and index.
hza 29/08/2018, ijb 07/02/2019
Loans
Keywords: Public investments; Capital; Government business enterprises